Oral testosterone administration detected by testosterone glucuronidation measured in blood spots dried on filter paper - Peng, S. H.; Segura, J.; Farre, M.; de la Torre, X. (Clinical Chemistry, 2000)
Background: Blood sampling is not a common practice for sports drug testing. Our aim was to investigate whether dried blood spots on filter paper could be an alternative to plasma samples for monitoring steroid profiles in dope testing. Methods: We collected dried blood spots and plasma from six healthy Caucasian subjects after an oral 120-mg dose of testosterone undecanoate (TU). Nonconjugated testosterone, testosterone glucuronide (TG), androsterone glucuronide (AG), and etiocholanolone glucuronide (EtG) were measured by gas chromatography-mass spectrometry in both matrices. 17-Hydroxyprogesterone (17OHP) and luteinizing hormone (LH) also were measured in the plasma samples. For comparison, similar measurements were done on samples obtained from the same subjects given 25 mg of testosterone propionate (TP) plus 110 mg of testosterone enanthate (TE) intramuscularly after a wash-out period. Results: After oral TU intake, TG, AG, and EtG increased sharply, whereas nonconjugated testosterone did not change significantly. Results on dried blood spots correlated well with those on plasma. The TG/testosterone ratio in blood or plasma was verified to be a sensitive and specific marker (significantly increased for up to 8 h after intake; P <0.05) for oral TU intake but not for intramuscular administration of TP plus TE. Little suppression of plasma LH and 17OHP was observed after a single oral dose of TU. One subject did not show a significant increase of blood TG after oral TU intake. Conclusions: The measurement of glucuronide conjugates in blood and plasma samples is relevant for sports drug testing when analyzing the steroid profile. Dried blood spots collected on filter paper are a suitable alternative to plasma for detecting testosterone abuse.